Institutionalizing Community Empowerment in City Planning: An Analysis Of Surabaya’s Cas Program - Pancawardani, Nur Ratna Wulan Kartini; Mustofa, Amirul (PT. Anagata Sembagi Education, 2025)
This study investigates the contribution of the Cangkrukan Arek Suroboyo (CAS) Program to community empowerment particularly youth in the context of Surabaya’s urban development planning. In response to the multifaceted challenges posed by rapid urbanization, community participation has become a critical pillar in the formulation of inclusive and sustainable urban policies. The CAS Program represents an innovative participatory mechanism initiated by the Surabaya City Government to foster dialogic communication between citizens and local authorities, rooted in local cultural practices. Employing a qualitative research design, this study collected data through in-depth interviews, surveys, and document analysis. Findings reveal that community empowerment through the CAS Program encompasses five key dimensions: cognitive, psychological, organizational, socio-economic, and participatory. The program has demonstrated effectiveness in enhancing youth knowledge, self-efficacy, active engagement, and decision-making capacity at the grassroots level. Furthermore, CAS has fostered social cohesion, strengthened individual and collective capacities, and cultivated a participatory ecosystem that positions youth as agents of urban transformation. These findings suggest that the CAS Program can serve as a replicable model for sustainable and inclusive community empowerment in urban governance.